Identifying key sites for connecting jaguar populations in the Brazilian Atlantic Forest. (27th July 2017) - Diniz, M. F.; Machado, R. B.; Bispo, A. A.; Brito, D.
Abstract: Networks of protected areas play a key role for large carnivore conservation since habitat fragmentation and population isolation are strong threats for them. We evaluated the contribution of the Protected Jaguar Areas (PJAs) and other forest fragments (1217 patches) to habitat availability and connectivity for jaguars in the Brazilian Atlantic Forest. We used habitat availability indices to rank the PJAs and the forest fragments according to their importance to different aspects of landscape connectivity. We also analyzed the protection degree of the forest fragments with greater importance for connectivity. PJAs represented 37% of the total amount of habitat area and 34% of the equivalent connected area of the whole network, suggesting that PJAs contribute only modestly to the habitat availability and connectivity of the complete network. The individual classification showed that the majority of PJAs did not contribute expressively in terms of intrapatch connectivity (65%) or to the connectivity among other patches (74%). Twenty‐six forest fragments were identified by the rank analysis. They increased the equivalent connected area index of the PJAs network between 3.8 and 4.1 times. Nearly half of the connector fragments' area (44.4%) is not under any degree of protection, and 34.8% of them are under the protection of sustainable use protected areas (IUCN categories V–VI). As umbrella and/or flagship species, the effective protection of jaguars may also benefit other species. Therefore, results indicate that the inclusion of the connector fragments in more restrictive protection categories (strict protection protected areas), associated with active population and habitat management strategies, might enhance habitat connectivity and availability not only for jaguars, but also for many other species in the Atlantic Forest. Abstract : Habitat fragmentation and population isolation are severe threats for large carnivores. In this context, the situation of the jaguar in the Brazilian Atlantic Forest is critical. We evaluated the contribution of the protected areas network and other forest fragments to habitat availability and connectivity for jaguars in the Brazilian Atlantic Forest. We showed that the current protected areas network contributes only modestly to habitat availability and connectivity for jaguars. We identified 26 forest fragments that had great importance for interpatch connectivity. Nearly half of these fragments' area is not under any degree of protection. Our findings suggest that the current network of protected areas of the Brazilian Atlantic Forest needs to be complemented to improve habitat availability and connectivity for jaguars, and potentially for other species as well (Photo credit: Grasiela Porfírio).